Save some, lose some: Biological consequences of an unexpected wage cut - Simona Bejenariu; Andreea Mitrut (Uppsala University, Department of Economics, 2012)
Recent literature exploring fetal shocks has focused on the effects of exogenous, but rather rare and violent events (e.g., military conflicts, natural disasters, terrorist attacks) and found that in utero experience has scaring, life lasting consequences. In this paper we consider the effect of an arguably more common and milder shock generated by a major and unexpected, albeit temporary, wage cut policy that affected all public sector employees in Romania in 2010. Our main findings suggest an overall improvement in the health at birth (as measured by the low birth weight indicator) of the cohorts exposed to the shock. Moreover, we find significant improvements in health at birth exclusively for boys and not for girls. This effect seems to be driven by significant effects of males exposed to the shock early in gestation. Additionally, we also find a decreased male to female ratio at birth for the cohort exposed to the shock. Overall, our results are consistent with the so-called culling theory hypothesizing that maternal exposure to significant stress early in gestation selects against male frail fetuses and, as a result of this selection in utero, at birth, one should observe significant improvements in health outcomes in the male cohorts.
urn:nbn:se:uu:diva-168335
Keywords: I19; J13; J38; Z18; 330; wage cut; transitory income shock; neonatal health; selection in utero; Romania; Lohn; Schock; Mütter; Fertilität; Kinder; Gesundheit; Rumänien